The Application of User Experience Questionnaire to Evaluate Customer Experience When Using Digital Platform to Purchase Flight Ticket in Two Travel and Ticketing Digital Companies - Sudirjo, Frans; Damara Gugat, Rudy Max; Budi Utama, Ahmad Nur; Utami, Eva Yuniarti; Martis, Andi (Jurnal Sistim Informasi dan Teknologi, 2023)
This research aims to find out the results of the assessment and comparison of user experience in online airline ticket booking applications using the user experience questionnaire (UEQ). Data collection methods include using literature studies and distributing questionnaires. The sampling technique used in this research was a simple random sampling method with a total of 100 respondents. Validity tests and reliability tests are also carried out using statistical calculations and tools. Based on the average score assessment on each travel A and travel B application scale using the UEQ questionnaire, both applications have a good overall user experience (UX) level. In travel application A, the average score for each scale, such as attractiveness, is 2.6, clarity is 2.4, efficiency is 2.5, accuracy is 2.4, stimulation is 2.5, and novelty is 2.5, all of which indicate that this application scored above or at least equal to the established "excellent" threshold. Meanwhile, for travel application B, the average score on each scale also shows that this application reaches a good UX level. The average scores for the attractiveness scale were 2.4, clarity was 2.5, efficiency was 2.5, accuracy was 2.3, stimulation was 2.4, and novelty was 2.2, all meeting or exceeding the threshold value of "excellent." From these results, it can be concluded that travel has a good performance in providing a satisfactory user experience on the online airline ticket booking application. Although there are slight variations in the average scores on several scales between the two applications, both overall provide an excellent user experience based on evaluation using the UEQ questionnaire.